Increased 10-year cardiovascular disease risk in depressed patients with coexisting subclinical hypothyroidism - Zhao, Shuai; Zhang, Boyu; Han, Yuqin; Guan, Jianjun; Fang, Wenmei; Zhang, Hongqin; Wang, Anzhen (Frontiers in Psychiatry, 2023)
Depressive disorder (DD) and subclinical hypothyroidism (SHypo) were both confirmed to be related to cardiovascular disease (CVD) risk. The current study aimed to evaluate the 10-year CVD risk in depressed patients with and without comorbid SHypo and identify potential risk factors associated with CVD risk. We recruited 2395 inpatients with a diagnosis of DD. Venous blood samples were taken from all patients for lipid and thyroid hormones. Framingham Risk Score (FRS) was used to estimate the 10-year CVD risk. In the male group, patients with SHypo had higher BMI, LDL-C, TC and lower HDL-C levels than patients without SHypo. In the female group, patients with SHypo had higher BMI, LDL-C, TG, TC, UA and lower HDL-C, and FT4 than patients without SHypo. All patients with SHypo exhibited a higher 10-year CVD risk than patients without SHypo. Serum TSH levels, BMI, and HAMA scores were critical predictive variables for 10-year CVD risk in female depressed patients with comorbid SHypo. Our study suggests an increased 10-year CVD risk in depressed patients with comorbid SHypo. Serum TSH levels, BMI, and HAMA scores may help predict cardiovascular risk in female patients with SHypo.